Efektivitas Manajemen Lembaga Pendidikan Islam pada Jurusan PAI Fakultas Tarbiyah UIN Sunan Kalijaga Yogyakarta - Wibowo, Agus (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
This research aims to investigate the level of effectiveness of the management of Islamic education in the Department of Islamic Education, Faculty of Tarbiyah and Teaching, UIN Sunan Kalijaga Yogyakarta. The focus is on curriculum management component, infrastructure, governance, and public relations. This  is a quantitative research using survey as its technique. The subject of this research are the chairman and the secretary of the Department of Islamic Education, 28 professors, administrative staff, and 270 students. The data is collected through observation, documentation, interviews and  questionnaire. The data is analyzed using SPSS Program version 2.0. The results showed that in terms of management (1) the curriculum reached high level of effectiveness of 81,29%, (2) the infrastructures also leveled in high category of 80,08%, (3) governance leveled at good (74,13%), and (4) public relations reached high category of 76,88%.   Keywords: Management Of Islamic Education, Islamic Studies